The impact of the pandemic on young people’s risk behaviour: risky challenges - Pastore, Patrizio; Grippo, Gerarda (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The contribution analyzes the risky social challenges highlighted by the international press, implemented during the pandemic period with a pedagogical-communicative approach linked to the sociology of risk. The viral phenomenon of challenges is observed in human behaviours with narcissistic and self-harming traits typical of adolescence. It is related to the hybridization of the overlapping of the communication and social interaction space with its digital virtualization.